Lactic Acid Bacteria Exopolysaccharides Producers: A Sustainable Tool for Functional Foods - Prete, Roberta (Foods, 2021)
Lactic acid bacteria (LAB) used in the food industry, mainly for the production of dairy products, are able to synthetize exopolysaccharides (EPS). EPS play a central role in the assessment of rheological and sensory characteristics of dairy products since they positively influence texture and organoleptic properties. Besides these, EPS have gained relevant interest for pharmacological and nutraceutical applications due to their biocompatibility, non-toxicity and biodegradability. These bioactive compounds may act as antioxidant, cholesterol-lowering, antimicrobial and prebiotic agents. This review provides an overview of exopolysaccharide-producing LAB, with an insight on the factors affecting EPS production, their dairy industrial applications and health benefits.